Using Gamification in the English Classroom: Impact on Motivation and Learning Outcomes - Adrefiza, Adrefiza (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This study aims to explore the use of gamification in English classes and analyze its impact on student's motivation and learning outcomes. The research method used in this article is qualitative with a library research approach by analyzing data sources from various literatures. Data collection through scientific journals, books, research reports, and other related documents relevant to this research topic. Data analysis by juxtaposing theories and previous research findings. The study results show that gamification benefits students' academic performance in English classes and dramatically increases their motivation and enthusiasm for learning so that the learning outcomes are satisfactory. This research provides a new contribution to understanding how gamification can be applied in an educational context and valuable recommendations for educators and decision-makers to improve the quality of teaching English in educational environments.